Bone and cartilage condition in experimental osteoarthritis and hypothyroidism - Dmytriy Sergeevich Nosivets (Medicinski glasnik, 2022)
Aim: To investigate changes in bone and cartilage tissue during the use of non-steroidal anti-inflammatory drugs and paracetamol in experimental osteoarthritis and hypothyroidism by the markers CTX-I and CTX-II. Methods: The experiments were performed on 75 white nonlinear rats of both sexes, which recreated osteoarthritis and hypothyroidism. Experimental osteoarthritis was performed by single intra-articular administration of monoiodoacetic acid solution in the knee joint and experimental hypothyroidism was reconstructed by enteral administration of a solution of carbimazole. After the formation of the experimental models on the 42nd day of the experiment, the animals were divided into 14 groups and drug administration began daily for 5 days. The quantitative level of markers of blood serum was performed by specific kits, which are based on ELISA on 42 and 47 days of the experiment. Results: The degree of influence on degenerative-dystrophic processes in bone tissue, which was assessed by the level of the marker СTX-I in the serum of rats, the studied drugs were as follows: diclofenac sodium > ibuprofen > nimesulide = meloxicam > celecoxib > paracetamol. According to the degree of influence on degenerative-dystrophic processes in cartilage tissue, which were assessed by the level of marker СTX-II in the serum of rats, the studied drugs were as follows: nimesulide > celecoxib > meloxicam > ibuprofen > diclofenac sodium > paracetamol. Conclusion: Determination of the levels of CTX I and СTX II allows the evaluation of the bone and cartilage condition in experimental osteoarthritis and hypothyroidism.
Keywords: anti-inflammatory agents; cartilage; enzyme-linked immunosorbent assay; hypothyroidism; knee joint; osteoarthritis